Optical Gaussian Notch Filter Based on Periodic Microbent Fiber Bragg Grating - Ali, M.M.; Lim, K.S.; Becir, A.; Lai, M.H.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2014)
In this paper, we demonstrated an optical notch filter constructed from a periodic microbent fiber Bragg grating attained by using two copper-wire-wound slabs. In the reflection spectrum, sideband peaks are created as a result of mechanically induced modulation on the grating period, and a higher number of peaks are observed when greater modulation is applied. The peak wavelength spacing depends upon the period of microbending, which can be varied by changing the diameter of the winding wire or the angle of placement of fiber Bragg grating placed in between the two wound slabs. Moreover, the trend of Bragg transmission loss (BTL) for the transmission spectrum changes with the changing of modulation period and amplitude. The proposed technique is very stable, and it can be used as an optical Gaussian notch filter.